1-Heteroarylpropan-2-ones as inhibitors of fatty acid amide hydrolase: Studies on structure-activity relationships and metabolic stability. Issue 3 (1st February 2017) - Zahov, Stefan; Garzinsky, David; Hanekamp, Walburga; Lehr, Matthias
Graphical abstract: Abstract: The serine hydrolase fatty acid amide hydrolase (FAAH) catalyzes the degradation of the endocannabinoid anandamide, which possesses analgesic and anti-inflammatory effects. A new series of 1-heteroarylpropan-2-ones was synthesized and evaluated for FAAH inhibition. Structure-activity relationship studies revealed that 1 H -benzotriazol-1-yl, 1 H -7-azabenzotriazol-1-yl, 1 H -tetrazol-1-yl and 2 H -tetrazol-2-yl substituents have the highest impact on inhibitory potency. Furthermore, attempts were made to increase the limited metabolic stability of the ketone functionality of these compounds towards metabolic reduction by introduction of shielding alkyl substituents in proximity of this serine reactive group.